Radiologic Correlation of Pleural Effusion and Cardiomegaly in Pickwickian Syndrome: A Case Report - Daniel Pradana Andrian Wicaksono; Sudharmadji (Department of Radiology, Medical Faculty, University of Brawijaya, 2026)
Pickwickian syndrome is a severe obesity-related condition characterized by chronic alveolar hypoventilation that leads to progressive cardiopulmonary and metabolic dysfunction. A 35-year-old male with morbid obesity, weighing over 150 kg, presented with shortness of breath and lower-limb edema for one week. Radiologic findings revealed cardiomegaly, pleuropneumonic consolidation with pleural effusion, and venous dilatation of the lower limbs without thrombus formation. Laboratory evaluation showed neutrophilia and an elevated neutrophil-to-lymphocyte ratio indicating systemic inflammation. Blood gas analysis confirmed chronic respiratory acidosis with metabolic compensation. The patient was treated with non-invasive ventilation, weight control, and multidisciplinary follow-up, which led to clinical improvement. Radiologic assessment using chest radiography, echocardiography, and Doppler ultrasonography played a vital role in correlating cardiac and pulmonary abnormalities and identifying venous insufficiency. This case emphasizes the importance of comprehensive imaging in detecting the cardiopulmonary continuum of Pickwickian syndrome, enabling early diagnosis and targeted intervention to prevent irreversible complications.